2021
DOI: 10.3389/fneur.2021.803901
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Robot-Measured Upper Limb Kinematic Data From Stroke Patients Are Novel Biomarkers

Abstract: Background: The efficacy of upper-limb Robot-assisted Therapy (ulRT) in stroke subjects is well-established. The robot-measured kinematic data can assess the biomechanical changes induced by ulRT and the progress of patient over time. However, literature on the analysis of pre-treatment kinematic parameters as predictive biomarkers of upper limb recovery is limited.Objective: The aim of this study was to calculate pre-treatment kinematic parameters from point-to-point reaching movements in different directions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…In our previous analysis of the data (Goffredo et al, 2021), the error of the trajectory towards the body negatively affects the probability of increasing one class in the discharge Motricity Indexes. However, in the re-analysis of data with least squares multiple linear regression, we found that the error of the trajectory towards the body was a significant predictor of Motricity Indexes, which strongly correlate (r > 0.8 for the MI UL ) with the therapist-assigned ones (Figures 2, 3).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In our previous analysis of the data (Goffredo et al, 2021), the error of the trajectory towards the body negatively affects the probability of increasing one class in the discharge Motricity Indexes. However, in the re-analysis of data with least squares multiple linear regression, we found that the error of the trajectory towards the body was a significant predictor of Motricity Indexes, which strongly correlate (r > 0.8 for the MI UL ) with the therapist-assigned ones (Figures 2, 3).…”
Section: Discussionmentioning
confidence: 98%
“…The procedure consisted of a re-analysis of 66 inpatients with subacute stroke who were included in a 4-week ulRT and whose data had been examined in our previous studies with different aims (Goffredo et al, 2019;Goffredo et al, 2021). In particular, in Goffredo et al (Goffredo et al, 2021), a relationship was found between RMK measures at baseline and (clinical and RMK) data at the end of ulRT, considering each direction of movement separately (Goffredo et al, 2021), and revealing that a subset of kinematic parameters was correlated with the probability of rising one class in the Motricity Indexes (when considered as Frontiers in Bioengineering and Biotechnology frontiersin.org categorical variables). In contrast, in the present study, we developed models to predict Motricity Indexes at discharge from selected RMK features and found that the SSV and LOOCV validation procedures explained 54% and 71% of the variance in clinical scores at discharge respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, therapy focused on arm use makes sense for patients with high PANU scores but is certainly less suitable for patients with mandatory compensations. In the same way that kinematic data measured during robot-assisted therapy can help predict patient recovery [ 58 ], using valid kinematic variables measured with the Kinect has the potential to predict which patients are the most likely to benefit from a specific therapy, and thus optimise patient care.…”
Section: Discussionmentioning
confidence: 99%